EFFECT OF SPIRULINA SUPPLEMENTATION WITH ASSOCIATED AEROBIC TRAINING PROGRAM ON BODY COMPOSITION OF OVERWEIGHT COLLEGE STUDENTS - Bera, Rajib; Ghosal, Amitava; Ghosh, Badshah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Objectives: The aim of the study was to observed independent and synergistic effect spirulina and aerobic training on body composition. Methods: Total 40 sedentary male overweight college students were randomly selected and separated into four equal groups viz. Spirulina Supplementation, Spirulina supplementation with Aerobic Training, Aerobic Training and Control. Measuring criteria were Body fat percentage, Triglycerides and Body Mass Index. 12-week training protocol was introduced where 5gm Spirulina platensis tablets were fed every day for the supplementary and combined groups. Similarly, moderate intensity aerobic training was introduced 4 days per week for aerobic training and combined groups. One-way ANCOVA and Bonferroni post hoc comparisons were used to examine training effects within groups. Results: Body fat percentage, Triglycerides and Body Mass Index showed significant difference at 0.05 level after introduced all the training protocol. Conclusion: It was concluded from this study that all three experimental groups successfully reduced body composition parameters in overweight individuals.